Comparative Evaluation of the Cytotoxicity of Glyphosate-Based Herbicides and Glycine in L929 and Caco2 Cells - Truzzi, Francesca; Mandrioli, Daniele; Gnudi, Federica; Scheepers, Paul T. J.; Silbergeld, Ellen K.; Belpoggi, Fiorella; Dinelli, Giovanni (Frontiers in Public Health, 2021)
INTRODUCTION: Glyphosate, an amino acid analogue of glycine, is the most widely applied organophosphate pesticide worldwide and it is an active ingredient of all glyphosate-based herbicides (GBHs), including the formulation “Roundup”. While glycine is an essential amino acid generally recognized safe, both epidemiological and toxicological in vivo and in vitro studies available in literature report conflicting findings on the toxicity of GBHs. In our earlier in vivo studies in Sprague-Dawley rats we observed that exposure to GBHs at doses of glyphosate of 1.75 mg/kg bw/day, induced different toxic effects relating to sexual development, endocrine system and the alteration of the intestinal microbiome. In the present work, we aimed to comparatively test in in vitro models the cytotoxicity of glycine and GBHs. METHODS: we tested the cytotoxic effects of glycine, glyphosate and its formulation Roundup Bioflow at different doses using MTT and Trypan Blue assays in human Caco2 and murine L929 cell lines. RESULTS: Statistically significant dose-related cytotoxic effects were observed in MTT and Trypan Blue assays in murine (L929) and human (Caco2) cells treated with glyphosate or Roundup Bioflow. No cytotoxic effects were observed for glycine. In L929, Roundup Bioflow treatment showed a mean IC50 value that was significantly lower than glyphosate in both MTT and Trypan Blue assays. In Caco2, Roundup Bioflow treatment showed a mean IC50 value that was significantly lower than glyphosate in the MTT assays, while a comparable IC50 was observed for glyphosate and Roundup Bioflow in Trypan Blue assays. IC50 for glycine could not be estimated because of the lack of cytotoxic effects of the substance. CONCLUSION: Glyphosate and its formulation Roundup Bioflow, but not glycine, caused dose-related cytotoxic effects in in vitro human and murine models (Caco2 and L929). Our results showed that glycine and its analogue glyphosate presented different cytotoxicity profiles. Glyphosate and Roundup Bioflow cytotoxic effects are similar to the ones caused by other organophosphate pesticides (malathion, diazinon, chlorpyriphos).